2014
DOI: 10.1007/s00262-014-1544-9
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of tumour-infiltrating B cells and tertiary lymphoid structures: a novel anti-cancer treatment avenue?

Abstract: Combining different standard therapies with immunotherapy for the treatment of solid tumours has proven to yield a greater clinical benefit than when each is applied separately; however, the percentage of complete responses is still far from optimal, and there is an urgent need for improved treatment modalities. The latest literature data suggest that tertiary lymphoid structures (TLS), previously shown to correlate with the severity of autoimmune diseases or transplant rejection, are also formed in tumours, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 158 publications
2
49
0
2
Order By: Relevance
“…Up to date, most reports in the literature state a positive effect of TILs in respect to OS, relapse-free survival and association with favorable prognostic factors, as well as lower T-stage (8). High B-cell density is said to be associated with improved outcome in gastric, breast and colorectal cancer (9)(10)(11), as well as squamous cell carcinoma of the tongue (12), melanoma and hepatocellular carcinoma (5,13).…”
mentioning
confidence: 99%
“…Up to date, most reports in the literature state a positive effect of TILs in respect to OS, relapse-free survival and association with favorable prognostic factors, as well as lower T-stage (8). High B-cell density is said to be associated with improved outcome in gastric, breast and colorectal cancer (9)(10)(11), as well as squamous cell carcinoma of the tongue (12), melanoma and hepatocellular carcinoma (5,13).…”
mentioning
confidence: 99%
“…Some immune cells have pro-tumorigenic activity, whereas others are anti-tumorigenic. B lymphocytes have been ascribed both pro-and anti-tumorigenic activities [3][4][5]. Many functional types of B cells that affect tumor growth or dissemination have now been identified, including B cells that support Th1 cells and cytotoxic T lymphocytes, B cells that promote angiogenesis, B regulatory cells that both suppress T effector cells and support T regulatory cells, and B cells that express class-switched, affinitymatured antibodies [5].…”
mentioning
confidence: 99%
“…However, based on a limited cohort of 28 cases, our study revealed novel characteristics of TILs and thus establishes the presence of TLS in bladder tumours in addition to their significant association with MIBC. TLS containing [22,23]. In ovarian, colorectal, breast and lung cancer, intra-tumoural B cells or those located within organized TLS are associated with favorable outcomes suggesting there anti-tumour role whereas their increased numbers are negatively correlated with melanoma, prostate, renal cell and hepatocellular carcinoma prognosis [16,19,24].…”
Section: Resultsmentioning
confidence: 99%